Delta bilirubin: a sensitive and predictive marker for acute rejection in liver transplant recipients - Gupta, Deepa; Gupta, Aditi; Raizada, Arun (International Journal of Research in Medical Sciences, 2018)
Background: This study was aimed to investigate the diagnostic utility of delta bilirubin for acute rejection in liver transplant recipients. Methods: The present study was conducted on 80 patients (56 men and 24 women) who were admitted for a major operation of liver transplantation at super-speciality hospital, Medanta-The Medicity, Gurgaon. The average age of the patients was 43±19 years. Data was analyzed as mean, standard deviation; student t test by using statistical package for social sciences (SPSS) software. Sensitivity, specificity, positive predictive value and negative predictive value were calculated in percentage. Results: The result from the present study indicates that delta bilirubin had highest sensitivities of 93% whereas conjugated bilirubin has 43% while AST, ALT, GGT and ALKP had sensitivities of 61%, 81%, 80% and 31% respectively. There was a significant difference of delta bilirubin between rejection and non rejection transplant recipients. Conclusions: Our findings supported that the serial measurement of delta bilirubin would be a reliable marker for recognizing early rejection in liver transplant recipients.